BRO-SPEAK SLANG IN MIKE LACHER’S ON THE BRO’D - Yusita Astriana (Universitas Katolik Widya Mandala Surabaya, 2014)
This study discusses bro-speak slang found in Mike Lacher’s On the Bro’d. Bro-speak slang is slang which is usually used by American youngsters whose hobbies are chugging, partying, hanging out and getting drunk. They name their group bros. The members of the group are from middle to high social level families. They have the same belief that the most important thing in life is to enjoy themselves. Therefore, some of their parents do not support them financially. It focuses on thekinds of slang and the purposes of using slang in the novel. This research is descriptive in nature. It was conducted through the following steps: collecting, classifying, and analyzing the data. The data were obtained from a seminal novel by Mike Lacher entitled On the Bro’d. The population of this research was all of the sentences containing slang within them. To get the sample, this research applied total sampling. Therefore,all the data were analyzed one by one. To describe the kinds of slangreferential equivalent method is used andto determine the purposes of using slang pragmatic equivalent method is used. Based on their kinds, slangs included sexual slangs, criminal slangs, slangs related to alcohol, drug slang, and slang related to money. In this case, sexual slangs were the highest frequency in use, while criminal slangs were the lowest. Moreover, based on the purposes of their use, slangs were used to express intimacy, express humor, show group identity, grade or score, show pleasure, degrade or put down, and keep secret. Most of the slangs were used to express humor, while just a few were to keep secret. Key Words : sociolinguistics, slang, bro-speak slang, kinds of slang, purposes of using slang